3D ultrasound DICOM data of the thyroid gland - Freesmeyer, M.; Darr, A.; Schierz, J.-H.; Schleußner, E.; Wiegand, S.; Opfermann, T. (Nuklearmedizin - NuclearMedicine, 2012)
Purpose: It has recently become possible to generate and archive three-dimensional ultrasound (3D-US) volume data with the DICOM standard Enhanced Ultrasound Volume Storage (EUVS). The objective of this study was to examine the application of the EUVS standard based on the example of thyroid ultrasound. Patients, methods: 32 patients, who were referred for thyroid diagnosis, were given a 3D-US examination of the thyroid gland (GE Voluson E8, convex 3D probe RAB4–8-D). The 3D data sets were exported to EUVS. Necessary additions to DICOM entries and transformation into an established DICOM standard were carried out. The visual assessment and volume measurements were performed by two experts on nuclear medicine using standard software in our hospital. Results: In 24/32 (75%) of the patients, the whole organ was successfully recorded in a single 3D scan; in 8/32 (25%), only part of organ could be covered. In all cases, 3D-US data could be exported and archived. After supplementing the DICOM entry Patient Orientation and transformation into the DICOM PET format, 3D-US data could be displayed in the correct orientation and size at any viewing workstation and any web browser-based PACS viewer. Afterwards, 3D processing such as multiplanar reformation, volumetric measurements and image fusion with data of other cross sectional modalities could be performed. The intraclass correlation of the volume measurements was 0,94 and the interobserver variability was 5.7%. Conclusion: EUVS allows the generation, distribution and archiving of 3D-US data of the thyroid, facilitates a second reading by another physician and creates conditions for advanced 3D processing using routine software
Keywords: Ultrasound; 3D ultrasound; thyroid gland; DICOM; image fusion